Cutaneous inoculation tuberculosis in a healthcare worker: Case report and literature review - Soto-Febres, F. (2020)
In all health care settings, particularly those in developing countries, healthcare workers have a high risk for exposure to tuberculosis. Tuberculosis can involve any organ, including the skin. Cutaneous tuberculosis is uncommon and may be secondary to an exogenous inoculation. We report the case of a surgical resident at a tertiary care hospital in Lima, Peru who developed cutaneous inoculation tuberculosis after sustaining a needlestick injury while performing a diagnostic cervical lymph node aspiration from a patient with HIV infection and tuberculous cervical lymphadenopathy.